Self-Management Applications For Improving The Productivity Of Adolescence At Risk Of HIV/AIDS - Herdiman, Herdiman; Lindayani, Linlin; Darmawati, Irma (Indonesian Journal of Community Development, 2021)
HIV/AIDS is a global health problem due to difficulty in spread detection. HIV spread is not visible directly, the symptoms will arise in 10-15 years. Adolescence is the period that is predicted as the highest exposure time in HIV. Self-management based on the mobile-phone app could be used to optimize the  adolescents’ protection ability in HIV/AIDS. This activity aims to improve adolescent soft skills on using cheap and effective mobile-phone apps to optimize adolescent productivity. Implementation methods are using online learning through video conference, focusing on the use of Self management applications: Smarter time on their activities and overview of HIV/AIDS. The results that they can understand the use of smarter time in time management and daily activity targets. Smarter time can be used as a reminder system. One of the recommended features is the focus mode that allows adolescents to manage the used apps in their mobile phones while being focused on activities without interruption of any other application activities especially social media. Increasing adolescent productivity also can increase positive behavior in leisure time and reduce the risk factors of HIV/AIDS.